Le reseau de betail trypanotolerant en Afrique de l'Ouest et en Afrique Centrale - Trail, J.C.M.; Murray, M.; Wissocq, Y.J. (1984)
Describes the background to the problem of trypanosomiasis in Africa, identifying Bos taurus & Bos indicus types of trypanotolerant breeds & discussing the importance of their use in the exploitation of tsetse-infested areas of Africa. Examines the establishment of a network of trypanotolerant livestock situations throughout West and Central Africa, & summarizes the current network situation, particularly w. respect to the productivity of trypanotolerant & trypano-susceptible breeds under dif. levels of risk & under dif. management regimes.